1991
DOI: 10.1149/1.2086017
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Response of Poly(3‐Methyl‐Thiophene) in Aqueous Solutions of Inorganic Salts

Abstract: Poly(3-methyl-thiophene) displays a pronounced sensitivity toward the dopant anions in aqueous solutions which is not observed in organic solvents. The voltammogram for the polymer in aquoeus solutions consists of two anodic peaks in the potential region 0-2 V. As demonstrated by in situ conductivity measurements, the first peak corresponds to the doping process, while the second peak, at more anodic potentials, is due to polymer degradation. The potential of the first current peak is strongly dependent on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 28 publications
1
6
1
1
Order By: Relevance
“…In-situ conductivity measurements employed a similar circuitry as that in Ref. 36 Thus, the working-electrode connection of a Wenking MP04 minipotentiostat was connected to one of the two gold plates of the in-situ conductivity probe (see above). We will refer to the gold plate to which the working electrode connection of the minipotentiostat was connected as the leading electrode.…”
Section: Methodsmentioning
confidence: 99%
“…In-situ conductivity measurements employed a similar circuitry as that in Ref. 36 Thus, the working-electrode connection of a Wenking MP04 minipotentiostat was connected to one of the two gold plates of the in-situ conductivity probe (see above). We will refer to the gold plate to which the working electrode connection of the minipotentiostat was connected as the leading electrode.…”
Section: Methodsmentioning
confidence: 99%
“…In this work we directly document changes in conductivity of electrochemically formed iridium oxide films (EIROF) with the use of an in-situ conductivity probe. [36][37][38] We also include ex-situ measurements of surface conductivity by current-sensing atomic force microscope (CS-AFM) and show that these are consistent with the direct assessment. Finally, we demonstrate how these measurements can be used to analyze the growth mechanism and electrochemical properties of EIROF in terms of the electronic structure.…”
mentioning
confidence: 52%
“…The anodic current peaks of PMT films in aqueous solutions of LiBF 4 , LiClO 4 , and LiCF 3 SO 3 (0.1 mol dm −3 ) are found at 720, 750, and 860 mV, respectively. Sunde et al [17] suggested that the specificity of PMT towards the different salts in aqueous solutions may be associated with the oxidizing power of the anions employed. The curves obtained with ClO 4 − and BF 4 − anions have similar shapes, whereas CF 3 SO 3 − produces a broader wave.…”
Section: Resultsmentioning
confidence: 99%